KOMUNIKASI PERSUASIF SATUAN LALU LINTAS (SATLANTAS) POLISI RESORT KOTA PEKANBARU DALAM MENINGKATKAN KESADARAN BERLALU LINTAS MELALUI PROGRAM POLICE GOES TO SCHOOL DI KOTA PEKANBARU - Murlan Hotmanian; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Police goes to school program is a socialization activity to schools driven by Satlantas Pekanbaru city to realize the attitude of discipline traffic on students. Increased traffic accident victims at a young age, Satlantas seeks to encourage students to care about traffic safety. Young age should be the next generation is very unfortunate if it must be a casualty accident. In fact, not infrequently we see reckless students become victims of accidents. Efforts are made is inseparable from the existence of persuasive communication activities so as to foster awareness for students to discipline in traffic. This study aims to determine the Selection of Communicators, Messages, Media, Target, and Persuasive Communication Techniques To Increase Traffic Awareness on Students in Pekanbaru City.This research uses qualitative descriptive method and persuasive communication model Applebaum & Anatol. The research informants consisted of ten people who were members of Dikyasa Satlantas unit Pekanbaru, teachers, and students using purposive and accidental sampling technique. Data collection techniques with in-depth interviews, observation and documentation. Data analysis techniques use interactive data models Miles and Huberman. To achieve data validity, researchers used extension of participation and triangulation.The results showed that Unit dikyasa Satlantas Pekanbaru has credibility as a communicator that can provide motivation about the importance of traffic discipline to students in the city of Pekanbaru. Persuasive message unit Dikyasa Satlantas Pekanbaru namely verbal messages include clarity, assignment, and accuracy and nonverbal messages. Media used is offline media using props, both online media that is facebook, instagram, siaganews.co and print media that is banner and banner. Target activities include elementary, junior high school, high school. and persuasive communication techniques include reward techniques, the use of humor, communication styles, asking and listening.Keyword: Persuasive Communication, Police Goes to School Program, Communication Model of Applebaum and Anatol